Penggunaan Strategi Inkuiri dalam Meningkatkan Hasil Belajar IPA Siswa SMP Negeri 5 Masbagik - Nuraini, Nuraini (TSAQOFAH, 2022)
The type of research used is Classroom Action Research (CAR). The purpose of this classroom action research (CAR) is to find out the extent to which student learning outcomes in science subjects are increased by applying the use of inquiry strategies. In class action research (PTK) this was carried out in 2 cycles, from the results of the actions taken it was proven to improve student learning outcomes by achieving the set classical completeness of 85%. Classical completeness in the first cycle of 70% with an average value of 75.8 can increase in the second cycle to 92% with an average value of 81.93. In terms of student activity, there was also an increase, namely in cycle I, the moderately active category increased to a very active category. The results of this action research show that the use of inquiry strategies can improve science learning outcomes with completeness reaching 92%.